Il principe ranocchio: note sul passaggio dall’infanzia all’adolescenza - Fagioli, Francesca; Telesforo, Ludovica (Il sogno della farfalla, 2018)
The article aims at illustrating the physiology and possible physiopathology of adolescents. The basic assumption is that in this fundamental phase in the life of a human being, a transformation at a psychic level takes place bringing about a new and sexually endowed human identity at the same time as a bodily revolution is taking place at the physical level. When this fusion between body and mind does not take place one’s thinking can become ill, affecting one’s affects and emotions and manifesting one’s malaise, at times, in forms of behavior that makes the crisis and the illness evident. It is important that, not only psychiatrists but general practitioners and pediatricians as well, who must often deal with the early phases of adolescent “malaise” which at times is not merely a simple “adolescent crisis”, be in a position to make not only a diagnosis but also a differential diagnosis. That is, they must be able to detect from small signs the type of mental illness and its seriousness, even when faced with an apparently non pathological clinical picture.